2020
DOI: 10.4102/ojvr.v87i1.1891
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for Trypanosoma evansi, the causative agent of surra, in the dromedary camel (Camelus dromedarius) population in Southeastern Algeria

Abstract: Surra, caused by Trypanosoma evansi , is a re-emerging animal trypanosomosis, which is of special concern for camel-rearing regions of Africa and Asia. Surra decreases milk yield, lessens animal body condition score and reduces market value of exported animals resulting in substantial economic losses. A cross-sectional seroprevalence study of dromedary camels was conducted in Algeria, and major risk factors associated with infection were identified by collecting data on animal characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
(81 reference statements)
3
7
2
Order By: Relevance
“…At the herd level, the overall seroprevalence rate of T. evansi infection was high (64.9%) in our study which revealed the wide spread of surra in the south of Tunisia which could be related to vector abundance in the study area. The result obtained by Benaissa et al was different from our finding indicating high seroprevalence rates of surra in camels in Algeria at the herd level ( Benaissa et al, 2020 ). The governorate of kebili has the high seroprevalence rate of T.evansi infection at the herd level.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…At the herd level, the overall seroprevalence rate of T. evansi infection was high (64.9%) in our study which revealed the wide spread of surra in the south of Tunisia which could be related to vector abundance in the study area. The result obtained by Benaissa et al was different from our finding indicating high seroprevalence rates of surra in camels in Algeria at the herd level ( Benaissa et al, 2020 ). The governorate of kebili has the high seroprevalence rate of T.evansi infection at the herd level.…”
Section: Discussioncontrasting
confidence: 99%
“…The seroprevalence of T. evansi varied significantly among governorates, and the governorate of Kebili seems to be the most affected with an infection rate of 37.5%. The high density of dromedaries and the presence of cross-border herd movement with Algeria could explain the high seroprevalence in this governorate ( Benaissa et al, 2020 ; Bouslikhane, 2015 ). Indeed, it was demonstrated that the seroprevalence of T.evansi in southern Algeria, an area bordering the governorate of Kebili, was assessed at 45% ( Benaissa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations